Method for producing partially expanded bodies with a pvc-based cellular structure and mould for their production - OLIVIER, GIACOMA (2001)
The present invention relates to a method for producing partially expanded bodies with a PVC-based embryo cellular structure comprising the steps of filling a plurality of moulds (1) with a paste containing PVC, loading these moulds (1) onto a press provided with heating and cooling means designed to subject the paste to the combined action of an increase in pressure and variation in temperature, expansion of the paste inside the moulds (1) and consequent forming of partially expanded bodies with an embryo cellular structure. In accordance with the present invention, during the expansion step, a step involving transfer of a first excess amount of paste from a main compartment (4) of the mould (1) to a secondary compartment (5) of the mould (1) takes place. This results in the formation, during the expansion and consequent forming step inside the main compartment (4), of a partially expanded main body with an embryo cellular structure and, inside the secondary compartment (5), of a partially expanded secondary body with an embryo cellular structure. The containing area (3) of the mould (1) is divided by a separation baffle (6) into two compartments, i.e. a main compartment (4) and a secondary compartment (5), communicating with each other by means of connection channels (8) formed on the separation baffle (6) itself.